The Pair-Bond Formation and Its Role in the Stimulation of Reproductive Function in Female Common Marmosets (Callithrix jacchus) - Silva, H.P. A. (1997)
SILVA, H.P.A.; SOUSA, M.B.C. The pair-bond formation and its role in the stimulation of reproductive function in female common marmosets (collithrix Jacchus). International Journal of Primatology, v, 18, n.3, p.387-400, 1997.